Grandchild care, inadequate medical insurance protection, and inequalities in socioeconomic factors exacerbate childhood obesity in China - Yang, Jing; Shen, Yun; Deng, Yue; Liao, Zangyi (Frontiers in Public Health, 2022)
This study examines the influences of grandchild care and medical insurance on childhood obesity. Nationally representative longitudinal data—from the China Family Panel Studies 2010–2020—of 26,902 school-age children and adolescents aged 6 16 years and China’s new reference standard (“WS/T586-2018”) are used to identify a child’s obesity status. Using binary mixed effects logistic regression models and the Blinder–Oaxaca decomposition method, this study explores the roots of obesity inequalities and finds that at least 15% of Chinese children aged 6 16 were obese in the 2010s. The logistic regression analysis results indicate that grandchild care, public medical insurance, and commercial medical insurance are key risk factors of child obesity. However, the influences are heterogeneous in different groups: Grandchild care and public medical insurance increase urban–rural obesity inequalities because of a distribution effect, and grandchild care may also exacerbate children obesity inequalities between left-behind and non-left-behind children owing to the event shock of parental absence. Inequalities in socioeconomic status (SES) factors such as income, education, and region also cause obesity inequalities. These results indicates that child obesity and its inequalities are rooted in multidimensional environmental inequalities, including medical protection policies and its benefit incidence; intergenerational behavior and family SES factors; and urban–rural and left-behind risk shocks. This study provides new evidence for the development of population-based interventions and equitable medical insurance policies to prevent the deterioration of child obesity among Chinese school-age children and adolescents.